Kant’s antinomies of pure reason and the "hexagon of predicate negation" - McLaughlin, Peter; Schlaudt, Oliver (Logica Universalis, 2020)
Based on an analysis of the category of “infinite judgments” in Kant, we will introduce the logical hexagon of predicate negation. This hexagon allows us to visualize in a single diagram the general structure of both Kant’s solution of the antinomies of pure reason and his argument in favor of Transcendental Idealism.
Gesehen am 16.10.2020